Exploring The Effect of Learning Environment on Students’ Mathematical Thinking Ability: Evidence from Matrix Learning at SMA Hang Tuah 1 Surabaya - Nathallia, Adhecristhiani; Anam, Fatkul; Emanuel, Endrayana Putut Laksminto; Kirana, Anik (MID Publisher International, 2025)
This study aims to determine the influence of the learning environment on the mathematical thinking skills of Phase F.11 students at SMA Hang Tuah 1 Surabaya in the context of matrix material. Mathematical thinking skills are essential abilities that need to be developed in mathematics learning because they relate to students' ability to reason, analyze, and solve problems logically and systematically. However, the results of the observations show that some students still have difficulty understanding the concept of matrices and applying them in problem-solving, which is thought to be caused by suboptimal learning environment factors. This study uses a quantitative approach with an explanatory research method. The research population comprised all students of Phase F.11 at SMA Hang Tuah 1 Surabaya. In contrast, the research sample consisted of 33 students from class F.11.3, selected via simple random sampling. The research instruments consisted of a learning environment questionnaire and a mathematical thinking ability essay test. Data were analyzed using simple linear regression in IBM SPSS Statistics version 26. The results of the study indicate that the learning environment has a positive and significant effect on students' mathematical thinking abilities, with a significance value of 0.001 < 0.05. The regression equation obtained is Y = 34.612 + 0.523X, which means that every one-unit increase in the learning environment score will increase mathematical thinking abilities by 0.523 units. The coefficient of determination (R²) of 0.541 indicates that the learning environment explains 54.1% of the variation in mathematical thinking abilities, while the remaining 45.9% is explained by other factors outside this study. Based on these results, it can be concluded that the better a student's learning environment —whether at home, school, or in the community —the higher their mathematical thinking skills, particularly in understanding and solving problems involving matrices. Therefore, improving the quality of the learning environment is a crucial factor in supporting successful mathematics learning in high school.